The "Miracles of Saint Menas" in the Armenian Tradition - Cichoń, Mirosław (Vox Patrum, 2025)
In this article, I aim to outline the Miracles of St Menas in the Armenian tradition. I describe the two available editions prepared by the Mekhitarists in Venice and outline the characteristics of the collection of manuscripts containing the works under study. On this basis, I correct the identification of miracles contained in BHO 748–750, namely De Agapio as Eutropius and the Silver Plates. In the further part, I provide a translation from Classical Armenian into English, accompanied by a commentary, of three miracles of St Menas preserved in the Armenian tradition: The Isaurian Pilgrim, Eutropius and the Silver Plates, and The Jew and the Christian.